THE USE OF COOPERATIVE INSTRUCTIONAL STRATEGIES TO CATER FOR THE LEARNING STYLE DIFFERENCES AMONG HIGH SCHOOL SCIENCE LEARNERS - Danso, Sakyiwaa; Mushayikwa, Emmanuel (Proceedings of the International Conference on Education, 2018)
The continuous use of the traditional method of teaching physical sciences in most senior secondary schools in South Africa and in particular schools in OR Tambo Inland District has contributed to the underperformance of learners in the subject. This has called for a shift from teacher-centered to a progressive learner-centered approach based on inclusiveness and collective learning to encourage diversity of reception and information processing. Therefore, this study investigated the use of Cooperative Instructional Strategy, considering learners learning style preferences to enhance learner’s achievement in electricity and magnetism. A pragmatic Mixed-methods sequential design was adopted for the study. The choice of mixed methodology was meant for both methods to complement each other for the purpose of data triangulation. Purposive sampling technique was used to select two high schools within the OR Tambo Inland District of Mthatha. Learning style questionnaire, physical sciences achievement test, interview, and observation schedules were the main instruments used to collect data. The quantitative data were analysed descriptively, while the qualitative aspect was analysed through thematic content analysis. It was found that cooperative instructional strategies improved learners’ performance in physical sciences. It is therefore recommended that teachers utilise appropriate instructional strategies that cater for all the differences learners bring to the classroom for effective teaching and learning to take.